Թուրքիայի հարավկովկասյան քաղաքականության արդի դրսևորումները - Հովսեփյան, Արմինե (YSU Journal of International Affairs, 2014)
In the context of geopolitical processes, occurring in the South Caucasus after the collapse of the USSR, Turkey's aspiration to penetrate the region of geopolitical and geostrategic importance for her, gaining control over the regional processes, promotion of its own scripts and projects, and positioning itself as a regional superpower is worth mentioning. Developing the tactics of its geopolitical influence expansion in the South Caucasus official Ankara at this stage continues to implement a consistent policy of strengthening its positions in Azerbaijan and Georgia by effective usage of military - political and economic as well as foreign policy levers (thus seeking to declare itself not only a regional but also a global power, able to influence the political processes of the South Caucasus and the  Caspian - Central Asian region as well). Based on the abovementioned, the possible formation of strategic alliance of Turkey, Azerbaijan and Georgia, which will deepen the dividing lines of the South Caucasus, thus finally displacing Armenia out of the regional processes is alarming.
Keywords: Turkey, foreign policy, South Caucasus, energy policy, military and political cooperation, economic expansion, Azerbaijan, Georgia, Meskhetian Turks, Javakhk, Armenia, Armenian-Turkish relations